Interleukin-1beta-induced reduction of tissue water diffusion in the juvenile rat brain on ADC MRI is not associated with 31P MRS-detectable energy failure. Issue 1 (December 2016) - Saggu, Raman
Abstract Background It has long been known that an intrastriatal microinjection of the archetypal pro-inflammatory cytokine, interleukin-1beta (IL-1β), in juvenile rats induces a chronic reduction in the apparent diffusion coefficient (ADC) of tissue water on magnetic resonance imaging (MRI). Reduced ADC during acute cerebral ischaemia is an established indicator of metabolic failure whereas the cause of the IL-1β-induced reduction remains to be deciphered. Previously, it has been shown that IL-1β does not perturb the phosphorus (31 P) magnetic resonance spectroscopy (MRS)-detectable energy status of anex vivo preparation of rat brain parenchyma that is devoid of a functional vasculature component. However, brain energy status following an IL-1β challenge in vivo remains to be examined. Methods This study is the first longitudinal in vivo examination of the correlation of ADC MRI with localised31 P MRS signals obtained specifically from within the injected and non-injected striatum following IL-1β (1 ng/ul or 100 ng/ul) challenge, in real-time. Results Despite observing a chronic reduction in ADC at either dose of IL-1β challenge, energy compromise was not detected at any time point. Conclusions The IL-1β-induced effects pertaining to a functional vasculature such as leukocyte recruitment, blood–brain barrier (BBB) breakdown and blood flow changes are unlikely to impact on overall tissue energy status. Compared to classic ischaemia, there is dissociation between ADC and energy status within an IL-1β-induced lesion in vivo.